Quantity -intensity relationship and fixation of phosphorus in soils from shrimp farming areas of coastal India - Muralidhar, M; Gupta, B P; Jayanthi, M (Indian Journal of Fisheries, 2011)
In the coastal environment, phosphorus release from bottom sediment plays a great role in its cycle. The availability of phosphorus in soil is controlled by the fixation mechanism. Laboratory incubation experiments were conducted with shrimp pond soils collected from Digha and Canning (West Bengal), Nellore (Andhra Pradesh), Muttukadu and Mahabalipuram (Tamil Nadu) and Mangalore (Karnataka) to determine the phosphorus fixation and quantity/ intensity relationship. The clay content was the major factor responsible for phosphorus fixation and it was high (62.1 %) in soil from Canning with 45 % clay and 8.05 pH followed by the soils from Mangalore (47.2%) having 39 % clay and 4.9 pH and silt loam soil from Nellore (39.9 %). Phosphorus fixation was positively correlated with clay (r = 0.96), calcium carbonate (r = 0.68) and silt (r = 0.24) and negatively correlated with phosphate potential (r = - 0.399) and available phosphorus content (r = - 0.313) in the soil. The average phosphate potential and equilibrium phosphate potential did not differ in soils except for acid soil, reflecting more or less similar availability of phosphorus, given the quantity of phosphorus in soils is nearly equal.